Salmon HNF1: cDNA sequence, evolution, tissue specificity and binding to the salmon serum albumin promoter. - Deryckere, F.; Byrnes, L.; Wagner, A.; McMorrow, T.; Gannon, F. (Journal of Molecular Biology, 1995)
cDNA clones coding for the transcription factor HNF1 have been isolated from Atlantic salmon (Salmo salar L.). The 559 amino acid residue long encoded protein shows high conservation, with respect to other species, of the domains necessary for DNA-binding: the HNF1 atypical homeodomain, the POU related sequence and the dimerisation domain. Alignment with rat HNF1 protein reveals that the transcription activation domains ADI and ADIII are relatively conserved in the fish sequence whereas ADII is not. Phylogenetic analysis indicates that higher vertebrate HNF1s and the related variant HNF1s (vHNF1s) are more closely related to each other than any of them is to Salmon HNF1, suggesting that the duplication event from which HNF1 and vHNF1 genes arose occurred after the divergence of the tetrapod and teleost ancestors. Northern blot analysis show a single transcript, of about 2.6 kb, which is not exclusive to liver but is also present in intestine, kidney and spleen. Using polymerase chain reaction (PCR) we have isolated the salmon albumin gene promoter which contains, upstream of the TATA box, a potential binding site for HNF1. The salmon HNF1 protein synthesized by in vitro transcription-translation of the full-length cDNA is able to bind specifically with equivalent affinities to either the rat or salmon albumin promoter.